2020
DOI: 10.1590/1678-460x2020360403
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal critical discourse analysis of the cinematic representation of women as social actors

Abstract: In this paper, an expanded version of the visual social actor network (van Leeuwen 2008) is suggested in integration with the classification of fields proposed by Martin (1992). In the context of multimodal critical discourse analysis, such network has provided a template for the discussion of the data aiming to reveal and interrogate the construal of women’s agency in the introductory part of the first film Sex and the City (2008). Overall results place women’s actions mostly in the private sphere but also re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…Critical Discourse Analysis by Theo van Leeuwen examines the processes of exclusion and inclusion found in media discourse [43]. Theo van Leeuwen delves into a comprehensive exploration of how media discourse, such as the language used in various forms of communication like news articles, advertisements, or television broadcasts, can shape and reflect societal dynamics through the intricate mechanisms of exclusion and inclusion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Critical Discourse Analysis by Theo van Leeuwen examines the processes of exclusion and inclusion found in media discourse [43]. Theo van Leeuwen delves into a comprehensive exploration of how media discourse, such as the language used in various forms of communication like news articles, advertisements, or television broadcasts, can shape and reflect societal dynamics through the intricate mechanisms of exclusion and inclusion.…”
Section: Resultsmentioning
confidence: 99%
“…Social actors are mentioned clearly but can also be mentioned incoherently or anonymously [43]. This anonymity can occur due to pressure from others who want the perpetrator to be constructed anonymously [46].…”
Section: ) Determination -Indeterminationmentioning
confidence: 99%
“…Furthermore, Fairclough stated that by using languages as social practices, the social practice dissolved essentially into language usage. Meanwhile, the other Critical Discourse Analysis model emphasizes the point views of actors, feminism, critical language, and social cognition which do not meet this study's aims (Bezerra 2020, Rafiqa 2020, Fowler & Kress 2023. This study uses Fairclough discourse analysis by analyzing all the news texts on the Tirto.id flood from 2019-2021 into three stages; namely the stages of microanalysis, meso analysis, and macro analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis indicated that the females in the two stories passed through challenging situations in order to revolt against the confines of their traditional binary roles. In movies, Bezerra (2020) explored the role of women as social actors in the movie Sex and the City, and the findings indicated that women were only depicted within the confines of their social norms. Differently, Constanty, Verônica, and M. Heberle (2021) employed a critical multimodal analysis to analyze the verbal-visual synergy used in three recent fairytales which present the deconstruction of their binary positions despite their different backgrounds.…”
Section: Gender Representations In Mediamentioning
confidence: 99%